Chemical Composition, Antibacterial Test, and Antioxidant Activity of Essential Oils from Fresh and Dried Stropharia rugosoannulata - Lei Wei; Wei Wang; Yueying Hou; Xiaoyang Xie; Xiao Li; Fei Chen; Zhiyao Wang; Yong Zhou; Feifei Li; Bingnian Jing (Journal of Chemistry)
The essential oils, respectively, from fresh and dried Stropharia rugosoannulata fruiting bodies, an important edible mushroom, have been studied for their chemical composition, antibacterial capacity, and antioxidant activity. The essential oils were obtained by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC-MS) combined with Kovats retention index. The oils’ antibacterial test was evaluated by the microdilution method against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa, and antioxidant activity was determined through DPPH radical scavenging activity and ferric reducing power. Twenty-nine components were identified from the fresh mushroom, and the compositions were mainly dominated by hydrocarbons (54.72%), acids (32.99%), esters (5.07%), and terpenic compounds (0.96%). Thirty-five components were identified from the dried sample, and acids (31.22%), terpenic compounds (28.7%), alcohols (12.7%), and ketones (10.48%) were the major compounds. Strong antibacterial capacity and obvious antioxidant activity were observed for both essential oils from the fresh and dried mushrooms.